Formação de professores de Matemática na modalidade a distância : um olhar sobre a práxis e a mediação didático-pedagógica em um curso de licenciatura da UFPA - Fernandes, Zenilda Botti (2016)
This research aims at the analysis of praxis and the didactic-pedagogic mediation of teachers (teachers, trainers and class tutors) who acted in the Distance Mode Course of Bachelor's Degree in Mathematics under the supervision of UFPA, linked to the UAB (Brazilian Open University). The provision of distance learning courses in the country, especially in the Amazon Region has been presented by the Education Ministry of Brazil (MEC - 2005) as an alternative to accelerate the expansion and qualification of the number of teachers with higher education and the improvement of basic education. Therefore, the relevance of this study is to examine conceptual elements that allow the understanding, weaving knowledge and deepening the reflections and questioning about the formation of mathematics teachers in distance education mode. The philosophical stance on the practice, allowed the understanding of the formation of mathematics teachers through the many experiences offered by the theory-practice relationship and the didactic and pedagogical mediation intensified by reflective processes. A historical and dialectical approach was adopted for the analysis and interpretation of bibliographical, documentary and oral sources, considering it more appropriate to the formative contexts put as dynamic, contradictory and historical; critical and transformational, which have their ontological and epistemological foundations in the practice and in the mediating. It is an investigation of the field of study of mathematics education which included the participation of teachers, trainers and class tutors from the nine main towns (pole) which ran the courses. Also, they show the existence of reiterative / traditional practice that coexisted with reflective and reiterative practice in teaching methodology and assessment of learning. The practice focused on the internship stage, from the 5th block of subjects and has been translated as imitation models and as technical instrumentation, causing the hierarchy and the dichotomy between theory and practice in training. It was clearly seen the presence of industrial and informational paradigms in the distance education model adopted by the course in linking to the educational planning that is prepared by the teacher trainer and executed by the class tutor, combining communication and interaction in the processes of teaching and learning. The research also pointed out that the face tutorials and courseware were the center of mediation carried out by the tutors, since students depended on the technological support of the poles to share the assignments of the subjects. Other results showed that the course was vulnerable to federal government funding policies, with impact on the continuity of the program. However, a look back at the course allows for the checking of the contributions to the qualification of teachers in the part of the Amazon Region that is located in Pará State as for distance contexts. Because it is so recent, its history is in the process of consolidation, and the confrontation of the challenges also indicates new paths and educational opportunities for innovation, in line with the social demands of the region.